User Authentication in the Public Areas of Academic Libraries in North Carolina - Stoffan, Mark A. (2015)
The clash of principles between protecting privacy and protecting security can create an impasse between libraries, campus IT departments, and academic administration over authentication issues with the public area PCs in the library. This research takes an in-depth look at the state of authentication practices within a specific region (i.e., all the academic libraries in North Carolina) in an attempt to create a profile of those libraries that choose to authenticate or not. The researchers reviewed an extensive amount of data to identify the factors involved with this decision.